ANALYSIS OF IRRIGATION WATER QUALITY INDEX AND EVALUATION OF LAND SUITABILITY IN DRYLAND IRRIGATION SYSTEMS AS EFFORTS TO OPTIMIZE AGRICULTURAL PRODUCTIVITY - Luthfi Inayah; I Putu Gustave Suryantara Pariartha; Silvia Gabrina Tonyes (Jurnal Ilmiah Teknik Sipil, 2025)
The availability and quality of irrigation water is an important factor in ensuring the sustainability of agricultural productivity, especially in drylands that are prone to drought such as in Abang District, Karangasem Regency, Bali. This study aims to analyze surface water quality for irrigation and evaluate land suitability through a comparative approach between the National Sanitation Foundation-Water Quality Index (NSF-WQI) method and the Index of Surface Water Susceptibility to Pollution (IKAPP). Surface water samples from Tukad Nyuling were analyzed based on physical and chemical parameters, and land suitability evaluation was also conducted by considering soil characteristics, such as permeability. The results showed that NSF-WQI values ranged from 69.96 to 79.78 within moderate to high limits while IKAPP water quality index values ranged from 23.69 within low vulnerability limits, this could be due to salinity constraints and contaminant indicators. A comparative rational analysis was then conducted which indicated that NSF-WQI is more suitable for use in the study area because it is able to capture variations in water quality that correlate with local physical, hydrological, and agroecological conditions. Integration of NSF-WQI results with land evaluation resulted in specific land management recommendations as well as crop suitability classifications, such as corn, green beans, chili, and other horticulture. This study concludes that in addition to being a representative measure of irrigation water quality, the application of the analysis supports efforts to improve less suitable land, through measures such as crop suitability evaluation, salinity management, and soil permeability improvement, thereby increasing agricultural productivity and supporting sustainable dryland management in Abang Sub-district.